Motor imagery and action observation of whole-body movements for experienced motor repertoire: an fNIRS study - Hayaka Yokota; Keita Kamijo; Nobuaki Mizuguchi; Hiroko Kubo; Hiroki Nakata (Japanese Society of Physical Fitness and Sports Medicine, 2023)
The present study used functional near-infrared spectroscopy (fNIRS), and investigated the characteristics of hemodynamic responses of oxy-Hb and deoxy-Hb during motor imagery and action observation for whole-body movements. Sixteen female participants performed tasks under two conditions: motor imagery and action observation. Each condition included three tasks of whole-body movement of gymnastics: (1) forward roll, (2) backward roll, and (3) cartwheel. Under both motor imagery and action observation conditions, the mean amplitude of oxy-Hb in the left posterior parietal cortex (PPC) was significantly more positive for the forward roll than cartwheel. The mean amplitude of deoxy-Hb was significantly more negative for the cartwheel than forward roll in the middle PPC. These findings suggest that PPC plays an important role in representations of movement during motor imagery and action observation. In addition, correlations between the vividness of motor imagery and mean amplitudes of oxy-Hb were identified in the premotor and primary motor areas. These results suggest that psychological assessments for vividness are linked to neural motor processes, and may provide a valid and economic tool to evaluate a person's ability to perform motor imagery.